Tantangan Dan Kesulitan Guru, Orang Tua Dan Siswa Dalam Pelaksanaan Pembelajaran Tatap Muka pada Era New Normal Pandemi Covid-19: Indonesia - WIRDA NINGSIH; Asmidar yani; Elmira wati (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The Covid-19 pandemic has changed the way student learning It was originally carried out through the face-to-face method to online learning. Teachers and students face new challenges and begin to adapt to the implementation of learning during the Pandemic. Through KSB (Joint Decree) 4 Ministers on December 21, 2021, the government decided to begin PTM ( limited face-to-face learning) from January 2022. This study aims to find out what are the difficulties and challenges that teachers must face in implementing face-to-face learning after the Covid pandemic -19. The method used in this research is a qualitative approach. The data in this study were obtained from interviews and observations of teachers and students of MI Al-Kifayah Riau. Difficulties and challenges that must be faced by teachers are the difficulties in training students to consistently maintain health protocols, limited learning time, learning loss (loss or decline in students' knowledge and abilities), decreased motivation and interest in learning, there is no clarity on the rules for implementing the curriculum in the new normal era. Students also have difficulty getting up in the morning and getting ready to go to school, and can not study on a regular learning schedule.